Effects of Nano Silver Particles and Gibberellic Acid on Growth and Some Physiological Characteristics of Dalbergia Sissoo Roxb. - Swara, Bahra J.; Al-barzinji, Ikbal M. (Science Journal of University of Zakho, 2021)
Recent studies show that Nanotechnology can be effectively used to enhance the characteristics of many types of trees including forest trees. Dalbergia Sissoo Roxb., which belongs to the Fabaceae family, is a forest tree that grows in dry land and water conservation areas. The aim of this study is to examine the effect of nano silver (NS) at (0, 30, 60 and 90 mg/L) and gibberellic acid (GA3) at (0, 50, 100 and 200 mg/L) concentrations on seed performance and subsequent growth of Dalbergia sissoo Roxb. The results reveal the enhancement of germination rate and velocity by using GA3 at 100 and 200 mg/L. NS90 treatment increased each of shoot and root fresh and dry weight, leaf area and plant height whereas GA50 treatment increased number of branches per plant and primary root length. Non-significant differences between treatments on Peroxidase enzyme activity and chlorophyll a content was observed whereas NS30 had the highest chlorophyll b and lowest total carotenoids. Shoot and root contents of some essential and non-essential elements differed between treatments. In roots, N90 treatment increased each of Cu and Mn elements, but it decreased Cl content. Although GA100 treatment increased Cl content, it decreased Mn. The paper concludes that the applications of nano-silver and GA3 on Dalbergia sissoo Roxb. have significant effects on its growth and physiological parameters.